Pengembangan Phantom Bantuan Hidup Dasar Sederhana sebagai Alat Bantu Praktikum Resusitasi Jantung Paru - Yas Suriani; Santa Novita Yosephin Silalahi (Jurnal Ilmu dan Teknologi Kesehatan Terpadu)
Typically, practical laboratory activities employ teaching media such as phantoms or props. Due to the increased demand for borrowing and utilization of laboratory equipment, as well as the presence of nursing laboratory standards, the Educational Laboratory Staff (PLP) is compelled to devise innovative solutions to address the shortage of instruments. One such solution is the Basic Life Support (BHD) phantom. The study aimed to create a straightforward Cardiopulmonary Resuscitation (CPR) model for Basic Life Support (BHD) training, utilizing manikin displays and indicator lights. The tool fabrication process began with rudimentary materials yet yielded comparable advantages to commercially available tools, enhancing the efficacy of practical tasks in laboratory experiments, research endeavors, and community outreach initiatives. The research employed the Research and Development Study approach and was conducted in the D3 Nursing Study Program laboratory at Poltekkes Kemenkes Tanjungpinang. The research process consisted of three distinct stages: tool design and assembly, trial phase, and tool acceptance or feasibility testing. The findings of this study demonstrated that the straightforward BHD phantom was deemed practical and suitable as an instructional tool in BHD training, specifically for Cardiopulmonary Resuscitation (CPR).   Future researchers must advance the development of this straightforward BHD phantom learning media to enhance the current prototype.